Vertically associated energy storage configuration of new energy power stations based on mixed integer nonlinear programming algorithm - Liu, Tian; Ren, Xiaoyong; Feng, Guoming; Shen, Linhui (Journal of physics. Conference series, 2025)
Traditional new energy power plants allocate energy storage based on a fixed proportion of installed capacity, resulting in low efficiency. Therefore, a new energy storage allocation method based on a mixed integer nonlinear programming algorithm is proposed, which integrates power generation characteristics, charging and discharging strategies, and grid constraints and iteratively optimizes to find the optimal solution. The experiment shows that this method performs well in terms of frequency deviation, grid-connected power smoothness, and charge discharge efficiency.